Anticoagulation during ECMO in neonatal and paediatric patients. Issue 173 (January 2019) - Barton, Rebecca; Ignjatovic, Vera; Monagle, Paul
Abstract: Extracorporeal Membrane Oxygenation (ECMO) is a form of Extracorporeal Life Support (ECLS) which is used frequently in the paediatric and neonatal setting to support either the pulmonary, or both the pulmonary and cardiac systems. Management of ECMO requires the use of systemic anticoagulation to prevent patient and circuit based thrombosis, which in turn increases the risk of haemorrhage. A number of coagulation tests, laboratory and point of care based, are used to monitor anticoagulation, however the evidence for correlation of the test results with level of anticoagulant and clinical outcomes in children remains poor. Highlights: A review of the pathophysiology, anticoagulation management in paediatric and neonatal ECMO. The choice of anticoagulation, monitoring and therapeutic targets varies worldwide. Further research is required into the haemostatic changes during paediatric ECMO.